Multimedia Interaktif dengan Penstimulasian Intelegensi Visual Spasial pada Submateri Ikatan Kovalen - Qurrota Ainyn; Kusumawati Dwiningsih (Jurnal Riset Pendidikan Kimia (JRPK), 2020)
This study aims to examine the feasibility of interactive multimedia by stimulating spatial-visual intelligence in terms of validity in covalent bonding material. This research refers to the Research and Development model according to Sugiyono's model which is only limited to design revisions. The validity results obtained interactive multimedia on covalent bonding material consisting of material that is in accordance with the curriculum and the material in accordance with learning material that has an average value of 80.00% validity with valid criteria. While the construct validity which consists of media indicators as multimedia, interactivity, the ability to stimulate visual intelligence, spatial competitiveness contributes to the average validity percentage of 81.33%, 82.22%, and 86.67%. Based on the results of the study it can be concluded that interactive multimedia on covalent bonding material deserves a review from the aspect of validity Keywords Interactive multimedia, spatial-visual, covalent bond, validity